The Effect of Visioner Leadership, Communication and Organizational Culture on Employee Commitment and Their Implications on Employee Performance - Pasaribu, Donald Frensius (Almana : Jurnal Manajemen dan Bisnis, 2024)
Facing competition in the current era of globalization requires every organization to work more efficiently and effectively. Competition Increasingly stringent conditions cause organizations to be able to increase their competitiveness in achieving the goals and objectives set by the organization. one of which is increasing employee commitment This study aims to know, analyze, and examine the influence of visionary leadership, communication, and organizational culture on employee commitment and its implications on employee performance at PT. Saraswanti Group North Sumatra. The research methods used are descriptive and verifiative analysis. The data collection used is using questionnaires accompanied by observation techniques and literature. The study used samples taken from proportionally selected employees. Data analysis techniques used to use SEM analysis. The results of the study descriptively show that visionary leadership, communication, organizational culture, employee commitment, and employee performance are in the category of quite good. The results of the verification research show that visionary leadership, communication, and organizational culture affect employee commitment both simultaneously and partially, and employee commitment affects employee performance at PT. Saraswanti Group North Sumatra.